Efeito da estimulação transcraniana por corrente contínua anódica sobre o controle do movimento em para-halterofilistas - Rego, Jeferson Tafarel Pereira do (2014)
Introduction: The sport practiced by people with disabilities has been growing in recent years. Consequently, advances in assessment and training methods have emerged. However, the paralympic sport keeps in tow these advances, with few specific studies that consider disability as intervening factor. The transcranial direct current stimulation (tDCS) is a technique that has proven to be capable of modulating brain function. Studies show beneficial effects of tDCS on muscle strength, power and fatigue during exercise. Objective: Investigate de the effect of tDCS on movement control in para-powerlifters. Methods: Eight subjects underwent two sessions of motion capture, which previously applied the anodic tDCS or sham sessions in the cerebellum. Three movements were performed with increasing load between 90-95% of 1MR. The movements were recorded by an 10 infrared cameras system which reconstructed the 3D trajectory of markers placed on the bar. Results: There have been changes between the anodic and sham conditions over bar level (initial, final, maximum during the eccentric and concentric phase) and in the difference between the final and initial bar level. Moreover, there was difference in bar level (final and during the eccentric phase) comparing athletes amputees and les autres. Conclusion: The findings of this study suggest that tDCS applied prior to the exercise over the cerebellum in para-powerlifters acts differently according to disability